PERSPECTIVE OF CATTLE DEVELOPMENT SCHEME IN TUBAN-EAST JAVA - Kuntoro Boga Andri; Rita Indrasti; Nugraha Pangarsa (Agricultural Socio-Economics Journal, 2016)
Tuban is one of primary areas of beef cattle development in East Java, Indonesia. However, poor food quality and cement as well as lack of good breeding result in slow development of livestock population in the regency. Moreover, the attempt to support beef self-sufficiency in Tuban was less than expected. The implementation of cattle development policies caused this to happen. This research used analysis of dynamic system which including the following phases: (1) developing causal loop diagram, (2) identifying and collecting quantitative data, (3) generating stock and creating flowchart in Powersim, (4) validating data, and (5) conducting simulation. The purpose of this research was to establish the policy and programme of beef cattle commodity development in Tuban. The research results show the mportant aspect of the development program which are: (a) Maintaining Tuban reputation as one of primary cattle product supplier across East Java and nationally (expected until 2021 with downward trend); (b) Increasing cattle population target up to 50 %, improving ineffective feed and production patterns; (c) Achieving beef production surplus up to 2012. From these results, some policy suggestions are: (1) maintaining/ boosting cattle population, (2) suspending beef/ cattle product imports, (3) developing value and benefits of derivative products such as bio-industry or otherwise waste utilization used to improve activities in agricultural sector.